L2 Motivational Self System and L2 achievement: A study of Indonesian EAP learners - Subekti, Adaninggar Septi (Universitas Pendidikan Indonesia, 2018)
This study was conducted to find the relationship between learners’ L2 Motivational Self System (L2MSS), consisting of Ideal L2 Self, ought-to L2 Self, and L2 Learning Experience and their achievement. The participants of this quantitative study were 56 Indonesian undergraduate students who were taking English for Biotechnology class, an English for Academic Purpose (EAP) class. This study was conducted based on several rationales. Despite many researchers’ support on L2MSS’ strength in predicting L2 learning, they have not conclusively established the extent to which learners’ motivation measured with their L2MSS influences their achievements and to date, there have only been few studies investigating the relationships between L2MSS and actual learning achievements. Besides, despite L2MSS’ growing popularity in the field of motivational research, motivational studies using L2MSS in the Indonesian university context are generally still very rare. Hence, this study can serve to pave a way for further motivational studies using L2MSS in the context. The study found that in general learners had high a level of motivation as measured with L2MSS questionnaires. The study further found several results which were rather surprising. First, Ideal L2 Self and L2 Learning Experience did not have significant relationships with achievement. Even ought-to L2 Self and achievement correlated negatively. It was also found that, despite many experts’ support on L2MSS’s strength in predicting L2 learning, the participants’ L2MSS could not be a strong predictor of their achievement. Based on the results, discussions on possible contributing factors were presented along with the implications of this study results in the field of motivational studies. Based on the possible limitations of the study, furthermore, some directions for future studies are also presented.